Distal nephron nephrosis - Rivera Felices, Julio (2014)
The distal nephron nephrosis is one of the outstanding problems that have arisen interest in medicine. Originally, it seems, by German researchers trying to differentiate nephritis trenches special nephrosis straight to muscle comprehension, which was observed during the First World War and Hackrad in 1917, called "Glass motorischene fhose" indicating the importance of motor vagus alteration in pathology and tubular injury. Later it was studied with various names because of the etiological differences that were observed; was termed parenchymal acute nephritis, acute tubular nephritis, renal syndrome anoxia, blackwater nephrosis, acute renal failure, renal anoxia regarding toxic syndrome and traumatic causes. Lately, Kimmiltein considered within the name nephrosis tubular nephrosis.